Landasan Filosofis Kesadaran Mahasiswa terhadap Kualitas Hidup - Renata Azalia; Rania Moniqa Triananda; Sekararum Putri Bermuda; Rifqi Dwi Sasmita; Mohammad Faishal Dzaky; Lutfi Hardiyanto (Damai : Jurnal Pendidikan Agama Kristen dan Filsafat, 2025)
Awareness of personal health is very important in improving the quality of life, especially among students who are in a transition period from adolescence to early adulthood. This research aims to understand more deeply about human health which includes physical, mental, and social aspects. By increasing students' awareness of personal health, it is hoped that it can improve their overall quality of life. The research also highlights the importance of students' understanding of social and historical developments, which can contribute to their well-being as well as create social responsibility. Health awareness involves not only paying attention to the body, but also the role of social and mental relationships in maintaining a balance in life. In this context, the philosophy of health, including ontology and existentialism perspectives, provides insight into the responsibility of individuals towards their life choices. By developing better awareness, students are expected to be better able to manage their physical, mental, and social health, so that they can achieve a more meaningful and quality life.